OAS and the transition to democracy in Haiti: the effort to restore President Aristide - Wilson, Larman C. ([The author] WashingtonUS, 1993)
Explains and analyzes the role and efforts of the OAS to support Haiti's transition to democracy and to deal with Aristide's overthrow and return to office. Considers the new basis for more immediate and stronger action in response to military coups - the 'Santiago Commitment to Democrary'. Presents recommendations for ending the impasse. Notes the actions of the OAS against Francois Duvalier in the 1960s.